Augmented Reality, Virtual Reality and their effect on learning style in the creative design process - Chandrasekera, Tilanka; Yoon, So-Yeon (Design and Technology Education: An International Journal, 2023)
Research has shown that user characteristics such as preference for using an interface can result in effective use of the interface. Research has also suggested that there is a relationship between learner preference and creativity. This study uses the VARK learning styles inventory to assess students learning style then explores how this learning preference affect the use of Augmented Reality (AR) and Virtual Reality (VR) in the creative design process.